Treg cells as potential cellular targets for functionalized nanoparticles in cancer therapy. (October 2016) - Jonuleit, Helmut; Bopp, Tobias; Becker, Christian
Treg cell-mediated immune suppression appears to represent a significant barrier to effective anticancer immune responses and their inactivation or removal is viewed as a potential therapeutic approach. Although suitable tools for selective Treg cell manipulation in man are missing, their number and function can be altered by a number of drugs and biologicals and by reprogramming tumor-infiltrating antigen presenting cells. Nanoparticles offer exceptional new options in drug and gene delivery by prolonging the circulation time of their cargo, protecting it from degradation and promoting its local accumulation in cells and tissues. In tumor therapy, the use of nanoparticles is expected to overcome limitations in drug delivery and provide novel means for cell-specific functional alteration. In this perspective, we summarize strategies suitable for interference with Treg-mediated suppression, discuss the potential use of nanoparticles for this purpose and identify additional, unexplored opportunities.